2011
DOI: 10.1093/eurheartj/ehr361
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function assessment: flow-mediated dilation and constriction provide different and complementary information on the presence of coronary artery disease

Abstract: Endothelial function assessment provides modest but statistically significant additional information in predicting the presence of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 24 publications
3
65
2
8
Order By: Relevance
“…In contrast to our findings and those of Spiro et al, Gori found that subjects with coronary heart disease have a low L-FMC measured at radial artery compared with those without coronary heart disease, although the magnitude of L-FMC did not discriminate subjects with different number of diseased vessels 13) . However, looking at the descriptive table, subjects without coronary heart disease had a comparable prevalence of some cardiovascular risk factors and were taking fewer drugs (statins, ACE-inhibitors, nitrates) compared with subjects with coronary disease.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings and those of Spiro et al, Gori found that subjects with coronary heart disease have a low L-FMC measured at radial artery compared with those without coronary heart disease, although the magnitude of L-FMC did not discriminate subjects with different number of diseased vessels 13) . However, looking at the descriptive table, subjects without coronary heart disease had a comparable prevalence of some cardiovascular risk factors and were taking fewer drugs (statins, ACE-inhibitors, nitrates) compared with subjects with coronary disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors have described radial artery vasoconstriction during low flow and suggested that this is an additional marker of endothelial function [11][12][13][14][15][16] . However, the low-flowmediated vasoconstriction (L-FMC) seems to be specific to the radial artery because it has not been consistently described for the brachial artery.…”
Section: Ultrasound Study Proceduresmentioning
confidence: 99%
“…brachial vs. radial arteries. The technique of measuring L-FMC also differs in cuff position; most authors place the pneumatic cuff distal to the side of arterial diameter measurement 29) , while others use the proximal cuff occlusion method 30) . Low-flow-mediated constriction is calculated as the percentage decrease in arterial diameter in the last 30s of cuff occlusion (after 4.5 min of 5 min occlusion) as compared with resting diameter 31) ; however, FMD is determined in the 5 min following cuff deflation.…”
Section: Peripheral Arterial Tonometrymentioning
confidence: 99%
“…Several studies have focused on the peripheral endothelial function and coronary artery disease [15,16,17]. Kuvin et al [15] found an association between coronary atherosclerosis and impaired endothelium-dependent vasomotion using high-resolution brachial artery ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%